Biologia reprodutiva de Cyphocharax modestus (Characiformes: Curimatidae) no rio Taquari (alto rio Paranapanema), São Paulo, Brasil - Perez, Isabelle Leite Bayona [UNESP] (2014)
The aim of this study was to analyze the reproductive tactics of the Cyphocharax modestus, a native fish of the family Curimatidae, at four different points distributed along the Taquari River and catchment area of the reservoir Jurumirim, Alto Rio Paranapanema, SP. The biological material was obtained through monthly collections made between September/2012 to August/2013 using of gillnets. Each specimen was measured for standard length (cm), was weighed (g) and dissected for macroscopic identification of sex. The gonads were weighed and macroscopically evaluated to their degree of maturation. The macroscopic gonad maturation was verified by histological analyzes, which were also assessed for spawning type and other details of reproductive biology. There was no sexual dimorphism and sex ratio showed no significant deviation from a 1:1 ratio. The CP50% of females of C. modestus was estimated at 7.1 cm, and histological evidence indicated to be a multiple spawner. The calculated values for RGS were higher for females and males average RGS of females was significantly higher in points located upstream relative to downstream points, which did not differ. For both males and females, a pattern of decreasing RGS values towards downstream was found, showing that the region of the upper Rio Taquari is a spawning area of this species. Seasonal variation of RGS shows that reproductive activity is concentrated in spring and summer, with females showing higher values in spring and summer, while for males the highest values were recorded in spring, significantly higher than the other stations, which do not differ significantly each other. This is corroborated by the variation in the frequency of mature females, which was higher in the months of September and October and males in the months of September and December. The information presented in this work allows us to conclude that this species has a relatively long reproductive period, during periods ...